Field notes contributed by Peter P. Wickham, summer 1987 - Wickham, Peter P.et al (1987)
Summer report of birds contributed by Peter P. Wickham, with an attached list of other bird observers and their locations. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1987. Epson - sheet feed/flatbed